A case report with review of literature of a rare variant of midfoot dislocations (mid-Chopart dislocation): Combined naviculo-cuneiform and calcaneo-cuboid dislocation. (June 2021) - Genena, Ahmed; Abouelela, Amr; Fadel, Mohamed H.
Highlights: Naviculo-cuneiform and calcaneo-cuboid dislocation is a rare combination with few case reports in the literature. The mechanism of injury is usually plantar-flexion and abduction force directed to the forefoot. Open reduction is mandatory to reduce such injures. Long-term follow up is needed to detect any late post-traumatic arthritis. Abstract: Closed midfoot and Chopart dislocations are uncommon injuries. Moreover, a combination of these dislocations is extremely rare. A 30-year-old male presented to our emergency department with mid-Chopart dislocation (combined naviculo-cuneiform and calcaneo-cuboid dislocation). Adequate open reduction with dual approach (dorsomedial and dorsolateral) and fixation with K-wires were achieved. Although the patient had satisfactory functional outcome postoperatively, he developed midfoot arthritis 12 months later. This type of dislocation is not yet classified, with only few cases reported in the literature. Level of clinical evidence: 4.